Komunikasi Digital dan Perubahan Gaya Hidup Generasi Gen Z - Sari, Rosi Indah; Yuzima, Risa; Ardini, Rena (Sagita Academia Journal, 2025)
The rapid advancement of digital technology has significantly transformed communication patterns and influenced lifestyle changes within modern society, particularly among Generation Z. Digital communication, facilitated through social media, instant messaging platforms, and online applications, has become the primary medium for interaction and information exchange. Generation Z, who were born and raised alongside technological development, demonstrates a high dependency on digital devices in daily activities such as education, entertainment, work, and the construction of social identity. This study aims to analyze how digital communication shapes lifestyle changes among Generation Z and to identify both the positive and negative impacts resulting from this transformation. A sociological communication perspective is applied to understand the social changes caused by the shift from face-to-face communication to virtual communication. The findings suggest that digital communication not only enhances creativity and facilitates access to information but also compromises the quality of interpersonal interactions, alters social behavior, and increases reliance on technology. Therefore, this research provides a deeper understanding of how digital media functions as an agent of social change in shaping the dynamics of young generations in the modern digital era.